Potensi reproduksi dan morfometri lalat tentara hitam, Hermetia illucens (Linnaeus) (Diptera: Stratiomyidae) yang dipelihara pada kotoran ayam dan kotoran domba: Reproductive potential and morphometry of the black soldier fly, Hermetia illucens (Linnaeus) (Diptera: Stratiomyidae) reared on chicken and sheep manure - Julita, Ucu; Kinasih , Ida; Andini, Dwinda (Jurnal Entomologi Indonesia, 2023)
Livestock manure such as chicken and sheep manures causes environmental problems such as odor pollution and pathogens found in livestock manure are harmful to animal and human health. The black soldier fly (BSF) have the ability to convert various types of organic waste effectively including livestock manure. Information on the reproductive potential and morphometry of BSF reared on livestock manure is still lack, as important data for optimizing the use of BSF to manage livestock manure. This study aims to determine the reproductive potential and morphometry of BSF reared on sheep and chicken manures. This experimental study used completely randomized design with three treatments, consist of chicken manure, sheep manure, and chicken feed as control. The development time, morphometry, mating frequency, and BSF fecundity were assessed. The sheep manure treatment had the highest development time among other treatments. Adult BSF morphometry reared on the chicken feed had the highest morphometric values compared to the chicken manure and the sheep manure. BSF reared on chicken feed had the highest number of mating pairs (44 pairs) compared to those treated with sheep manure (31 pairs) and chicken manure (20 pairs). The highest egg fecundity was found in BSF treated with chicken feed (3,535 eggs). These suggested that chicken manure and sheep manure are suitable as growth media for BSF, while its reproductive potential is lower compared to chicken feed.